Institutional betrayal and sexual harassment in STEM institutions: evidence from science and technology universities of Ethiopia. Issue 2 (17th February 2022) - Sidelil, Leul Tadesse; Cuthbert, Denise; Spark, Ceridwen
ABSTRACT: In this paper, we examine the experiences of female students and academics to understand the factors that underpin the persistence of sexual harassment in science, technology, engineering and mathematics (STEM) institutions. We draw on data from interviews and focus group discussions with female students and academics who participated in a study that focuses on gender inequality in science and technology universities in Ethiopia. Drawing on the concept of institutional betrayal, we argue that the high prevalence of sexual harassment in these universities is perpetuated by institutional actions and inactions through which universities fail to proactively prevent and effectively respond to sexual harassment. We suggest efforts to tackle sexual harassment need to focus on proactive and preventive measures that involve revisiting institutional policies and structures. We further suggest that grievance procedures need to be accessible, responsive, trustworthy and supportive.